2021
DOI: 10.1111/1440-1703.12202
|View full text |Cite
|
Sign up to set email alerts
|

Elevation and aspect determine the differences in soil properties and plant species diversity on Himalayan mountain summits

Abstract: Although vegetation has been the focus of recent studies on mountain summits, little is known about smaller‐scale spatial patterns of soil physico‐chemical properties. Here, we report patterns and drivers of soil physico‐chemical properties and their role in shaping the plant diversity on mountain summits of the Himalaya. Using the globally standardized Multi‐Summit Approach, four summits along an elevation gradient from treeline to nival zone were selected in Kashmir Himalaya. Sampling of the summits was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 65 publications
3
16
1
Order By: Relevance
“…Micro-climatic conditions may vary significantly over short spatial scales in mountainous areas due to the steep environmental gradients and thus substantially influence vegetation distribution and species richness patterns (McCain and Grytnes, 2010). Hamid et al (2021) found significant differences in the edaphic properties along elevation gradients and changing aspects in their study. They also discovered that aspect play an important role, in addition to elevation, in determining the survival of plant populations in mountainous areas.…”
mentioning
confidence: 91%
“…Micro-climatic conditions may vary significantly over short spatial scales in mountainous areas due to the steep environmental gradients and thus substantially influence vegetation distribution and species richness patterns (McCain and Grytnes, 2010). Hamid et al (2021) found significant differences in the edaphic properties along elevation gradients and changing aspects in their study. They also discovered that aspect play an important role, in addition to elevation, in determining the survival of plant populations in mountainous areas.…”
mentioning
confidence: 91%
“…These results indicate that the difference in bacterial b-diversity was due to the dominant species, whereas in fungi was due to rare species. Theoretically, different plant characteristics and soil environments can create different niches (Hamid et al, 2021), and, consequently, affect specific soil microbial communities (Pot et al, 2022). In the current study, bacterial b-diversity was driven mainly by plant a-diversity and root biomass, but fungal b-diversity was driven mainly by AK and SBD.…”
Section: Effect Of Herbivore Assemblage On Microbial a And B Diversitymentioning
confidence: 52%
“…This raises the question of whether correlations with climate variables for these species on the elevation gradient could be misleading, because their ranges extend beyond the elevations that many biogeographic studies 10.3389/fevo.2022.942759 in this region of the Himalaya have measured. Many studies have sought climate and environmental drivers for patterns of species richness (e.g., Carpenter, 2005;Acharya et al, 2011;Manish et al, 2017;Rana et al, 2019;Hamid et al, 2021). Our study raises the question of how much influence do species with ranges that extend beyond the elevation gradient have upon the measures of species richness that are used as response variables in studies that correlate climate and environmental conditions with species richness patterns?…”
Section: Species Elevation Rangesmentioning
confidence: 89%
“…One region with relatively low species occurrence records is the eastern Himalaya, although many studies have used limited data to examine elevational patterns of woody vascular plant species, including Carpenter (2005), Behera and Kushwaha (2007), Acharya et al (2011), Kluge et al (2017), Manish et al (2017), Rana et al (2019), Sharma et al (2019), Tiwari et al (2020), and Hamid et al (2021). The majority of these studies seek to quantify mid-elevation species richness patterns, to associate environmental predictors with elevational patterns of species richness or turnover, or to differentiate elevational distribution patterns according to various plant traits including endemism and life form.…”
Section: Introductionmentioning
confidence: 99%